2018
DOI: 10.1002/cssc.201802235
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable and Antibacterial Two‐Dimensional Tungsten Disulfide Lamellar Membrane for Water Filtration

Abstract: Two‐dimensional (2D) lamellar membranes consisting of restacked WS2 nanosheets have shown excellent separation properties for water filtration. The stability, antifouling properties, and antibacterial activities of the WS2 laminar membranes were investigated for practical application. We discovered that the separation properties of the WS2 laminar membranes changed slightly after soaking in water for 28 days as well as that of a 45 h‐cross‐flow filtration, demonstrating an extraordinary operational stability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Nanosheets such as WS 2 or BN can be incorporated into polymer phase to form mixed‐matrix membranes with gas permeability and/or selectivity. The introduction of 10 % WS 2 into fluorinated poly(phenylene oxide) (FPPO) improved CO 2 permeability, CO 2 /N 2 selectivity, and CO 2 /CH 4 selectivity by 216 %, 148 %, and 137 %, respectively, because WS 2 provided transport channels for gas molecules . Similarly, introduction of functionalized BN nanosheets (1 wt %) into thermally rearranged polymers increased H 2 /CH 4 selectivity from 24.1 to 275 …”
Section: Applicationsmentioning
confidence: 99%
“…Nanosheets such as WS 2 or BN can be incorporated into polymer phase to form mixed‐matrix membranes with gas permeability and/or selectivity. The introduction of 10 % WS 2 into fluorinated poly(phenylene oxide) (FPPO) improved CO 2 permeability, CO 2 /N 2 selectivity, and CO 2 /CH 4 selectivity by 216 %, 148 %, and 137 %, respectively, because WS 2 provided transport channels for gas molecules . Similarly, introduction of functionalized BN nanosheets (1 wt %) into thermally rearranged polymers increased H 2 /CH 4 selectivity from 24.1 to 275 …”
Section: Applicationsmentioning
confidence: 99%
“…From these studies, it can be concluded that most of work has been carried out with graphene for finding the virus in body and diagnosing the patients. Furthermore, 2D materials such as MXene, TMDCs, MOFs, h‐BN also show good antibacterial properties 58–68. Therefore, future research should be carried out in this direction for better detection of pathogens including COVID‐19.…”
Section: Role Of Graphene‐based Materials Against Covid‐19mentioning
confidence: 99%
“…Nanosheets of TMDs such as WS 2 have been explored as membrane materials and can also play a role as nanofillers for TFN membranes. 126,127 Other emerging nanosheets such as MXene and COF are at a very primitive stage in research and development in terms of being used as nanofillers for TFN membranes. Their impact on the PA layer properties and membrane performance must be comprehensively evaluated and benchmarked against commercial membranes.…”
Section: Materials Advances Reviewmentioning
confidence: 99%